Bio-inspired micro-to-nanoporous polymers with tunable stiffness - Syurik, Julia; Schwaiger, Ruth; Sudera, Prerna; Weyand, Stephan; Johnsen, Siegbert; Wiegand, Gabriele; Hölscher, Hendrik (Beilstein Journal of Nanotechnology, 2017)
Background: Inspired by structural hierarchies and the related excellent mechanical properties of biological materials, we created a smoothly graded micro- to nanoporous structure from a thermoplastic polymer.Results: The viscoelastic properties for the different pore sizes were investigated in the glassy regime by dynamic flat-punch indentation. Interestingly, the storage modulus was observed to increase with increasing pore-area fraction.Conclusion: This outcome appears counterintuitive at first sight, but can be rationalized by an increase of the pore wall thickness as determined by our quantitative analysis of the pore structure. Therefore, our approach represents a non-chemical way to tune the elastic properties and their local variation for a broad range of polymers by adjusting the pore size gradient.
Keywords: biomimetics; polymeric materials; supercritical carbon dioxide (SC-CO2); tunable storage modulus